Large-scale use of fish traps for monitoring sea trout (Salmo trutta) smolts and sea lice (Lepeophtheirus salmonis) infestations: efficiency and reliability. Issue 1 (2nd January 2016) - Arechavala-Lopez, Pablo; Uglem, Ingebrigt; Berg, Marius; Bjørn, Pål Arne; Finstad, Bengt
ABSTRACT: Lice-infected sea trout populations were monitored using fish traps in the Romsdalsfjord (Norway). The reliability and efficiency of this capture technique, which allows estimation of lice infestation rates without killing the fish, was evaluated through a mark–recapture study. A total of 2447 sea trout smolts were captured, tagged and released over a three-year period. There was a considerable variation in capture rates (range: 0.4–17.7 fish per day) and sea lice numbers (number of lice per fish: 2.8–30.3; number of lice per gram body weight: 0.02–0.69) among localities, sampling times and years. Recapture rates of tagged fish with traps, which were low (2% or 0.11 fish per day), showed that the risk for pseudoreplication was minor, in terms of counting lice on the same fish several times. Most of the tagged sea trout (90%) were recaptured within the first two months after release, and no significant variations in lice numbers were found between tagging and recapture. The lack of differences in lice levels between tagging and recapture during the first week after tagging indicated that the method most likely would not significantly underestimate the lice infestations due to loss of lice during handling. Therefore, our results confirm that the use of fish traps is a suitable method for estimation of lice numbers on wild salmonids.